Eensydige vergifnis : 'n pastorale studie - Lusse, Gesina Christina (North-West University, 2009)
In this study the important issue of unilateral forgiveness is researched. Chapter one contains the problem, research questions, objectives, methodology and central theoretical argument which involves the following: the healthy (faith mature) treatment of unilateral forgiveness, in the absence of the offender's remorse, as a essential element in the healing process in recovering for the emotional wounded person. This is the reason why such a person should be guided pastorally. In chapter 2, the aspect of basic-theory is being looked into, which entails the following: The Old Testament example of forgiveness in Jonah, and also forgiveness and repentance in the New Testament, and four passages namely Luke 17:3-4, Matt 18:15,21-22; Mark 11-25 6:12-15 and Matt 6: 12-15 were discussed. Afterwards, penitence and forgiveness in Judaism and Christianity were also investigated where conditional and unconditional pardon came into question. The various dimensions of forgiveness -that is from the divine side, human side and intrapersonal were researched. Finally God's purpose for forgiveness was discussed. Chapter three fostered the meta-theoretical aspect of the study. A brief history was given of the psychology of forgiveness and the relationship between theology and psychology were examined. The definition of forgiveness also received attention in order to better understand the concept. The reason for forgiveness, and the consequences of anger, (a core element of unforgiveness) on the total person, the physical, neurological, psychological, and psychiatry sides were discussed. Attention were given to therapy where the process of forgiveness, with two different models were discussed namely Pyramid Model of Worthington and the Concept of proses model of Enright & Fitzgibbons. The chapter ends with reconciliation and inner preparation to unilateral forgiveness. In chapter four the empirical research received the focus, which included the value of empirical research, different paradigms, the choice of an approach, and the nature and characteristics of qualitative research. Thereafter, data collection, including basic personal interviews, parameters of the interview, questionnaire design, sampling design and identification of themes for interviews, got attention The discussion of the interview results were concluded with a preliminary conclusion from the empirical research to end this chapter. In chapter 5 attention was given to the practical theoretical perspectives with regard to unilateral forgiveness. Because Zerfass's model were used in the study, particular attention had been given to examining of the effect of Zerfass's model. Then a summary were given of the findings of Scriptural perspective, relevant sciences, empirical research and practical theoretical guidelines in brief. It concludes with a summarized report of findings in respect of unilateral forgiveness, practical theory and proposed guidelines. The study ended in chapter six where the final conclusion regarding the research on unilateral forgiveness were given and topics were proposed for further research.
Thesis (M.A. (Pastoral))--North-West University, Potchefstroom Campus, 2010.
Keywords: Unilateral; Forgiveness; Emotional; Injury; Pastoral; Unconditionally; Conditionally; Intrapersonal